Pengaruh Keterampilan Mengajar Menggunakan Aplikasi Bandicam terhadap Kriteria Ketuntasan Minimal (KKM) Siswa Mata Pelajaran PAI di SMA Islam Samarinda - Nur R, Dayu Rahmad (Borneo Journal of Islamic Education, 2022)
The Effect of Teaching Skills Using the Bandicam Application on Students' Minimum Completeness Criteria (KKM) in PAI Subjects at Samarinda Islamic High School". Thesis Department of Islamic Education, Faculty of Tarbiyah and Teacher Training, State Islamic University of Samarinda. The background of this research is regarding the implementation of teaching skills using the bandicam application which is carried out at the Samarinda Islamic High School, it is known that this location has an internet network connection that is difficult to reach. So that it can result in the minimum completeness criteria of students in Islamic religious education subjects being low or not reaching the standard. This type of research is a quantitative research. The research tool used is a research instrument in the form of a questionnaire. The results of this study obtained that the reliability calculation of the Cronbach's alpha questionnaire was classified as moderate, namely 0.924. In get the value of the coefficient of determination of 0.272. Results of research data analysis. Based on the t value: it is known that tcount is 5.321 > ttable 0.1927 so that Ha is accepted. In other words, the teaching skills variable (X) has an effect of 27.2% which is classified as weak on the minimum student completeness criteria variable (Y).